New insights into markers for distinguishing neuroendocrine prostate cancer: evidence from single-cell analysis - Luo, Hailang; Li, Boyang; Zhang, Meng; Wang, Hongqun; Hao, Zongyao; Ge, Qintao; Liang, Chaozhao (Frontiers in Immunology, 2025)
BackgroundNeuroendocrine prostate cancer (NEPC) is a highly aggressive malignancy with few effective treatment options. The identification of reliable biomarkers for NEPC is essential for early detection and intervention.MethodsWe combined single-cell and bulk transcriptome analysis to identify novel markers of NEPC. InferCNV to assess copy number variations and leveraging consensus non-negative matrix factorization (cNMF) to characterize transcriptional programs. Pseudotime analysis was used to decipher prostate cancer (PCa) progression differentiation trajectory. BayesPrism integrates single-cell results and TCGA-PRAD sequencing information to further study prognostic features. Immunohistochemistry (IHC) was performed to validate the elevated expression of ASCL1 and WDFY4 in NEPC.ResultsWe identified five distinct expression programs of PCa malignant epithelial cells, where Module 3 presented NEPC expression patterns, with activation of DNA replication and cell cycle pathways and classical NEPC marker expression. Patients with high Module 3 proportion correlated to poor clinical outcomes, advanced Gleason scores, and higher T stages. Pseudotime analysis highlighted key trajectory-dependent genes involved in the transition to NEPC, where expression of ASCL1 and WDFY4 elevated with progressing to NEPC cell fate, which were further confirmed by IHC analysis, indicating that WDFY4 and ASCL1 might be novel potential markers for distinguishing NEPC.ConclusionsCombined single-cell and bulk analysis, we highlight the cellular heterogeneity and transcriptional programs, validated novel biomarkers of NEPC. Providing a foundation for early prediction of NEPC and management.